An international survey of pelvic trauma surgeons on the management of pelvic ring injuries. Issue 10 (October 2021) - Parry, Joshua A; Funk, August; Heare, Austin; Stacey, Stephen; Mauffrey, Cyril; Starr, Adam; Crist, Brett; Krettek, Christian; Jones, Clifford B; Kleweno, Conor P; Firoozabadi, Reza; Sagi, Henry Claude; et al.
Highlights: The management of pelvic ring injuries is controversial with little agreement among the surgeons who care for them. 19 international pelvic trauma surgeons completed a 45-item questionnaire on the management of pelvic ring injuries. 38 (84%) of the 45 questions had minimal to no agreement among the respondents. A multi-center effort to develop a prospective pelvic trauma registry is needed to obtain better evidence to direct treatment. Abstract: Introduction: There exists substantial variability in the management of pelvic ring injuries among pelvic trauma surgeons. The objective of this study was to perform a comprehensive survey on the management of pelvic ring injuries among an international group of pelvic trauma surgeons to determine areas of agreement and disagreement. Methods: A 45-item questionnaire was developed using an online survey platform and distributed to 30 international pelvic trauma surgeons. The survey consisted of general questions on the acute management of pelvic ring injuries and questions regarding 5 cases: Lateral compression (LC) type 1 injury, LC-3, Anterior-posterior compression (APC) type 3 injury, a combined vertical shear (VS) injury through the sacrum, and VS injury through sacroiliac joint. Respondents were shown blinded anteroposterior pelvis radiographs and axial computed tomography (CT) images for each case and asked if the injury needed fixation, the type of fixation, the order of fixation, and postoperative weight-bearing status. The Kappa statistic was calculated to assess agreement between respondents for each question. Results: Nineteen out of 30 pelvic trauma surgeons completed the survey. Respondents practiced in Brazil ( n  = 1), Germany ( n  = 1), India ( n  = 1), Italy ( n  = 1) United Kingdom ( n  = 1), and the United States ( n  = 14). Of the 45 questions in this survey, 38 (84%) had minimal to no agreement among the respondents. There was moderate agreement, for performing lumbopelvic fixation when indicated, for anterior and posterior fixation of the LC-3 injury, and on forgoing EUA or stress X-rays for the APC-3 injury. There was strong agreement for open reduction and internal fixation of the anterior pelvic ring in the APC-3 injury and the VS injury through the SI joint. In contrast, LC-1 injury and combined VS pelvic ring injury through the sacrum had no areas of moderate to strong agreement. Discussion: This study identified specific areas of pelvic ring injury management with minimal to no agreement among pelvic trauma surgeons. Future research should target these areas with a lack of agreement to decrease practice variability and improve patient outcomes.